2011
DOI: 10.1002/pd.2717
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fetal cardiac structure and function detected by echocardiography in women with normal pregnancy and gestational diabetes mellitus

Abstract: Fetal cardiac wall thickness, cardiac systolic and diastolic functions are affected by GDM independently of glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 33 publications
(39 reference statements)
7
35
1
1
Order By: Relevance
“…Tissue Doppler was able to detect both systolic and diastolic dysfunction than conventional Doppler in infants of diabetic mothers with hypertrophic cardiomyopathy when compared to the control group. This higher sensitivity of tissue Doppler over the conventional Doppler was previously reported in various studies [20,29,30]. We also found that Tei index was more sensitive than left or right ventricle fractional shortening in detecting impaired cardiac performance.…”
Section: /9supporting
confidence: 71%
“…Tissue Doppler was able to detect both systolic and diastolic dysfunction than conventional Doppler in infants of diabetic mothers with hypertrophic cardiomyopathy when compared to the control group. This higher sensitivity of tissue Doppler over the conventional Doppler was previously reported in various studies [20,29,30]. We also found that Tei index was more sensitive than left or right ventricle fractional shortening in detecting impaired cardiac performance.…”
Section: /9supporting
confidence: 71%
“…In the US, up to 18% of all pregnancies are now affected by diabetes (52), and 35% of women are obese (23), a comorbidity that increases health risks (36). Infants born to obese or diabetic mothers are at higher risk of cardiovascular disease at birth (29,51,59) and throughout life (22,54), purportedly through fuel-mediated influences (5,10,24). Current preventative measures focus on glucose control (2).…”
mentioning
confidence: 99%
“…Hypertrophic cardiomyopathy observed in the infant of the diabetic mother is characterized by thickening of the interventricular septum, and to a lesser extent the ventricular free walls (Hornberger, 2006). The presence of this pathology whether is associated with fetal hyperinsulinaemia and general somatic growth in maternal diabetes (Buchanan & Kjos, 1999;Ren et al, 2011). But, the wide variety of cardiac abnormalities suggests a complex pathogenesis.…”
Section: Congenital Cardiopathies and Diabetes Mellitusmentioning
confidence: 99%
“…Experimental studies suggest that hyperglycemia is the major teratogen in diabetic pregnancies, but other diabetes-related factors may also affect fetal outcomes (Aberg at al., 2001;Buchanan & Kjos, 1999;Leonard et al, 1989;Ren et al, 2011). It is a fact that an uncontrolled diabetes mellitus in early gestation is associated with a teratogenic effect, causing primary cardiogenesis defects.…”
Section: Congenital Cardiopathies and Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation